Celebrating Susan MacMillan's contributions to ILRI - International Livestock Research Institute (International Livestock Research Institute, 2021)
Using photos and one-word descriptions from colleagues and friends, this photo film celebrates Susan MacMillan's contributions to ILRI over the years.